Inserção dos produtores na cadeia do leite e seu nível de produtividade : um estudo para a região sudoeste do Paraná - Zanmaria, Nelito Antonio (2010)
The aim of this paper is to study the Paraná Southwest region in relation to its milk production, the region is one of the most promising regions in the state. For this study, questionnaires were applied and with the aid of the clusters analysis methodology, three distinct groups were found which were formed in the region seeking to understand which factors explain the differences between them. Understanding that the agribusiness system chain leads to grounds which help the comprehension of these groups and analyze the formation and characteristics in Paraná State and the region offers notes and explanations which guide the analyses according to the characteristics and inspirations of the producers themselves. The results obtained show that there is a difference in thoughts between high and low productivity producers: while the high producers are specialized, have a higher output production output and are in the market for less time, the low producers are longer in the market, have a lower production and do not have a high degree specialization, considering that a certain percentage of producers are in the market for lack of choice. The Southwest region is growing, both in production and productivity and shows that the agribusiness system is important for the complete emancipation of the dairy sector.